2005
DOI: 10.1073/pnas.0501782102
|View full text |Cite
|
Sign up to set email alerts
|

CcbP, a calcium-binding protein from Anabaena sp. PCC 7120, provides evidence that calcium ions regulate heterocyst differentiation

Abstract: Although it is known that calcium is a very important messenger involved in many eukaryotic cellular processes, much less is known about calcium's role in bacteria. CcbP, a Ca 2؉ -binding protein, was isolated from the heterocystous cyanobacterium Anabaena sp. PCC 7120, and the ccbP gene was cloned and inactivated. In the absence of combined nitrogen, inactivation of ccbP resulted in multiple contiguous heterocysts, whereas overexpression of ccbP suppressed heterocyst formation. Calmodulin, which is not presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
86
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 39 publications
2
86
0
Order By: Relevance
“…In cyanobacteria, Ca 2ϩ is an essential part of the reaction centers of photosynthetic proteins and may also be a signal for differentiation during heterocyst formation (28,29). In the case of CmpA, calcium may be used to either increase the binding affinity or selectivity of bicarbonate over the other anions such as nitrate.…”
Section: Discussionmentioning
confidence: 99%
“…In cyanobacteria, Ca 2ϩ is an essential part of the reaction centers of photosynthetic proteins and may also be a signal for differentiation during heterocyst formation (28,29). In the case of CmpA, calcium may be used to either increase the binding affinity or selectivity of bicarbonate over the other anions such as nitrate.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that mature heterocysts and proheterocysts have an increased [Ca 2ϩ ] i (10). To understand the mechanism for regulation of [Ca 2ϩ ] i during heterocyst differentiation, we studied the kinetics of [Ca 2ϩ ] i increase during heterocyst differentiation.…”
Section: Degradation Of Ccbp By Hetr and The Release Of Bound Calciummentioning
confidence: 99%
“…CcbP, a calcium-binding protein in heterocyst-forming cyanobacteria, plays an important role in the regulation of [Ca 2ϩ ] i and is absent in mature heterocysts. The expression of ccbP is also down-regulated in heterocysts (10). However, it is not known at present how Ca 2ϩ is released from CcbP and how the expression of ccbP is regulated.…”
mentioning
confidence: 99%
See 2 more Smart Citations